Objects of Politics: The Appropriation of Earth Science Collections in Prussia during the Long Nineteenth Century - Angela Strauß (Museum & Society)
Research into the history of collections can shed light not only on the epistemic, but also the political and economic dimensions of the objects that museums collect. This article explores these dimensions through the study of acquisitions in the mineralogical collections of the Natural History Museum Berlin. During the nineteenth century, appropriation processes were increasingly shaped by economic arguments and political perspectives. After the German Empire became a colonial power in the 1880s, rocks and minerals from Africa, particularly Namibia and Tanzania, were seized. Ultimately, contemporary museums must take responsibility for their past collecting practices because their collections are built upon those practices.